Near hangings: Epidemiology, injuries, and investigations. Issue 3 (March 2019) - Schellenberg, Morgan; Inaba, Kenji; Warriner, Zachary; Alfson, Daniel; Roman, Jordan; Van Velsen, Valery; Lam, Lydia; Demetriades, Demetrios
Abstract : BACKGROUND: Near hangings are an infrequent cause of trauma, and the optimal workup for these patients is unclear. The study objectives were to define the epidemiology, injury patterns, and use of investigations, including computed tomographic angiography (CTA) neck, after near hangings. METHODS: All patients presenting to LAC+USC Medical Center (2008–2015) after near hanging ( International Classification of Diseases, Ninth Revision, code of E913.8, E953.0, E963, or E983.0) were screened for inclusion. Transferred patients were excluded. Patient demographics, clinical data, injury data, investigations performed, and outcomes were collected. RESULTS: Over the study period, 71 patients were identified. Median age was 32 years (interquartile range [IQR], 24-44), and 85% (n=64) were male. Median Glasgow Coma Scale was 12 [IQR 5-15], and median Injury Severity Score was 1 [IQR 1-2]. Mortality rate was 14% (n = 10). The most common finding on physical examination was a ligature mark (n = 38, 54%). Cervical injuries after near hangings occurred infrequently (five injuries in four patients [6%]: 3 [4%] arterial injuries and 2 [3%] laryngotracheal injuries). Only one patient (1%) required surgical and/or endovascular intervention. Two (3%) arrived in cardiac arrest, underwent resuscitative thoracotomy, and were pronounced dead. All others (n = 69, 97%) underwent CTA of the neck. No patient in this series manifested signs or symptoms of cervical injury during hospitalization after a normal CTA neck on presentation. CONCLUSION: Near hangings infrequently result in cervical injury, and intervention is rarely needed. When injuries are sustained, they occur to critical structures such as the larynx, trachea, and cervical vasculature. Therefore, effective injury screening is important. We recommend CTA of the neck as the optimal initial imaging investigation after near hangings. LEVEL OF EVIDENCE: Epidemiologic, level IV; therapeutic/care management, level IV.